Daughters of Darkness: Intertextuality in Le Fanu’s «Carmilla» and Gogol’s «Viy» - Romanets, M. (Гоголезнавчі студії, 2009)
Автор статті досліджує інтертекстуальні зв’язки «Камілли» Фану та «Вія» Гоголя крізь призму жіночих демонічних образів. Автор статьи исследует интертекстуальные связи «Камиллы» Фану и «Вия» Гоголя сквозь призму женских демоничеких образов. The author of the article explores the intertextual connetions in Le Fanu’s «Carmilla» and Gogol’s «Viy» through the female demon characters.